Effect of additives on the co-electrodeposition of Sn-Ag-Cu lead-free solder composition - Joseph, Shany; Phatak, Girish J. (Materials Science and Engineering B-Advanced Functional Solid-State Materials, 2010)
We have developed a methane sulfonic acid (MSA) based ternary electrodeposition bath for the deposition of near eutectic Sn-Ag-Cu films aimed at solder bumping applications in electronics. The bath contains thiourea as chelating agent and iso-octyl phenoxy ethanol (OPPE) as surfactant. We added gelatin to this bath and studied its effect on bath stability, microstructure of the deposited films and the film composition. It is found that the bath containing both the additives, viz. OPPE and gelatin, show improved stability up to 8-10 days. Striking improvement in the film microstructure, in terms of the compactness, uniformity and refinement of grains was found when the bath contained these additives. Detailed electrochemical studies with the help of cyclic voltametry and impedance analysis helped in understanding the role played by these additives during deposition. It is confirmed that there is a formation of loosely connected, highly non-uniform passivating film on the cathode surface, which is removed competitively by the depositing metal ions during the deposition. It is also clear that the additives play a role in the formation of such a passivating film. (C) 2010 Elsevier B.V. All rights reserved.
Keywords: Additives; Lead-free solders; Sn-Ag-Cu; Solder bumping; Ternary bath

Synthesis of low coercive BaFe12O19 hexaferrite for microwave applications in low-temperature cofired ceramic - Rane, Vivek A.; Meena, Sher Singh; Gokhale, Suresh P.; Yusuf, S. M.; Phatak, Girish J.; Date, Sadgopal K. (Journal of Electronic Materials, 2013)
Polycrystalline M-type barium hexaferrite (BaFe12O19) samples have been synthesized by solution combustion route at different pH and calcination conditions in order to reduce the coercivity for microwave applications in low-temperature cofired ceramic (LTCC) substrates. Structural, morphological, and magnetic properties of BaFe12O19 were studied by x-ray diffraction (XRD), field emission scanning electron microscopy (FESEM), Raman spectroscopy, vibrating sample magnetometry (VSM), and Mossbauer spectroscopy. The formation of a single-phase hexagonal structure was confirmed by XRD. The Raman spectra reveal all characteristic peaks of BaFe12O19, illustrating the phase purity and crystal lattice symmetry of the synthesized material. Mossbauer spectra illustrate the existence of Fe3+ cations at all five crystallographic lattice sites. The microstructural features observed by FESEM disclose the growth of nanoregime particles into hexagonal platelet particles after calcination at temperatures from 800A degrees C to 1200A degrees C. The VSM results show a lower coercivity (1350 Oe to 3500 Oe) together with reasonably high saturation magnetization (55 emu/g to 60 emu/g) and a high bulk resistivity (> 10(9) Omega-cm) at room temperature. The dependence of magnetic and electrical properties on the preparation and processing conditions is also discussed.
Keywords: Barium hexaferrite; coercivity; LTCC; Mossbauer spectroscopy; Raman spectroscopy